First clinical experience with esophageal ESD using a novel adjustable traction device - Miyazaki, Kurato; Kato, Motohiko; Sasaki, Motoki; Iwata, Kentaro; Masunaga, Teppei; Kubosawa, Yoko; Hayashi, Yukie; Mizutani, Mari; Takatori, Yusaku; Matsuura, Noriko; Nakayama, Atsushi; Takabayashi, Kaoru; Nakajima, Kiyokazu; Kanai, Takanori; Yahagi, Naohisa (Endoscopy International Open, 2023)
Background and study aims In esophageal endoscopic submucosal dissection (ESD), the effectiveness of traction including clip-thread method has been reported, but it is difficult to adjust the direction of traction. Therefore, we developed a dedicated over-tube type traction device (ENDOTORNADO) that has a working channel and allows traction from any directions by rotating itself. We investigated the clinical feasibility and potential usefulness of this new device in esophageal ESD.Patients and methods This was a single-center, retrospective study. Six cases of esophageal ESD with ENDOTORNADO from January to March 2022 (tESD group) were compared with 23 cases of conventional esophageal ESD performed by the same operator from January 2019 to December 2021 (cESD group) in terms of clinical treatment outcomes.Results In all cases, en bloc resection was achieved without intraoperative perforation. The total procedure speed was significantly increased in tESD group (23 vs. 30 mm2/min, P = 0.046). In particular, the submucosal dissection time was significantly reduced to about one-quarter in tESD group (11 vs. 42 min, P = 0.004).Conclusions ENDOTORNADO creates the adjustable traction from any directions and may have the clinical feasibility. It would be an option for human esophageal ESD.